AMBIENT MEDIA SEBAGAI KAMPANYE SOSIAL PENTINGNYA EDUKASI BAGI CALON ORANGTUA UNTUK ENCEGAHAN STUNTING DI MARIANA BANYUASIN 1 SUMATERA SELATAN - moh yogie pratama Khoiriyah; Yosef Yulius; Husni Mubarat (VisArt: Jurnal Seni Rupa dan Design, 2023)
Abstract : Stunting is a condition in children with failure to thrive or growth delays due to chronic malnutrition. Currently there is still a lack of understanding and anticipation for prospective parents related to stunting. Therefore, the author wants to provide an educational information medium that can inform and invite that stunting will have a very bad impact on children. in order to be able to provide awareness to prospective parents and be able to prepare for the birth of healthy and normal babies in South Sumatra. It is hoped that the purpose of this design is to serve as an educational and informational medium that can provide knowledge to all prospective parents as well as an information medium for all prospective parents to increase awareness of the dangers of stunting from an early age during pregnancy and also to raise awareness about stunting for prospective parents and specifically for pregnant mothers.